2020
DOI: 10.7324/japs.2021.110217
|View full text |Cite
|
Sign up to set email alerts
|

Exploring public health benefits of Dolichos lablab as a dietary supplement during the COVID-19 outbreak: A computational study

Abstract: The emerging case of coronavirus disease-19 (COVID-19) caused by the severe acute respiratory syndromecoronavirus (SARS-CoV-2) virus has become a global health issue. Since there is no available developed vaccine, health-promoting foods play a vital role in maintaining the immune system against the disease. Dolichos lablab (DL), an unutilized highly nutritional legume, has an excellent potential to cope with this pandemic with various health benefit phytochemicals. This study appraised the possibility of phyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Although other variants may exist, these three are commonly found in several regions in Indonesia, such as East Java (Probolinggo and Madura Island) and West Nusa Tenggara (Purwanti et al 2019b). The previous study reported the bioactivity of bioactive compounds and nutritional values of Lablab beans (Purwanti et al 2021;Purwanti et al 2022). Nevertheless, no report addresses the nutritional differences among the variants of Lablab beans.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although other variants may exist, these three are commonly found in several regions in Indonesia, such as East Java (Probolinggo and Madura Island) and West Nusa Tenggara (Purwanti et al 2019b). The previous study reported the bioactivity of bioactive compounds and nutritional values of Lablab beans (Purwanti et al 2021;Purwanti et al 2022). Nevertheless, no report addresses the nutritional differences among the variants of Lablab beans.…”
mentioning
confidence: 99%
“…Nevertheless, no report addresses the nutritional differences among the variants of Lablab beans. Lablab beans have numerous bioactivities including antioxidant (Maheshu et al 2013), antidiabetic (Purwanti et al 2022), antivirus (Purwanti et al 2021), antimicrobial (Bai-Ngew et al 2021, and anti-inflammatory properties (An et al 2020). These bioactivities make it a promising and excellent candidate for functional food development.…”
mentioning
confidence: 99%